Public health impact of adverse bone effects of oral corticosteroids. - van Staa, T; Abenhaim, L; Cooper, C; Zhang, B; Leufkens, H (2001)
AIMS: The objective of this study was to estimate the number of fractures attributed to oral corticosteroid use. METHODS: Information was obtained from the General Practice Research Database which contains medical records of general practitioners in the UK. The total number of corticosteroid-related fractures during a course of treatment was estimated using the formula for attributable risk among the exposed. RESULTS: A total of 244 235 patients was prescribed an oral corticosteroid. The rate of hip fractures increased exponentially with age in both males and females. The excess number of hip fracture cases among females aged 85 years or older using 7.5 mg prednisolone per day or more was 1.4 cases per 100 patients per year. About 47% of all hip and 72% of all vertebral fractures that occurred can be attributed to oral corticosteroid use. Among 10 000 female users of higher doses, 99.7 nonvertebral, 31.6 hip and 45.8 vertebral fractures can be attributed to use of oral corticosteroids. CONCLUSIONS: The targeting of high-risk patients will be important for implementing preventative strategies in a cost-effective manner.